Paths to middle-class mobility among second generation Moroccan immigrant women in Israel - Mizrachi, Beverly (Raphael Patai series in Jewish folklore and anthropology., 2013)
While first-generation immigrant women often begin their lives at the bottom of their new societies, the fates of their adult daughters can be very different. Still, little research has been done to examine the opportunities or constraints that second-generation women face and the class achievements they make. In this volume, the author presents an in-depth study of 40-50-year-old Moroccan women whose parents made up part of the largest ethnic group to enter Israel after its establishment in 1948 and whose mothers began their new lives at the bottom of the economic and social ladder. Through her analysis of the life history narratives of these women, the author reveals that they used a range and number of sites to achieve an impressive mobility into the low, middle, and high segments of the middle class.